2019
DOI: 10.1002/kjm2.12137
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of miR‐212 contributes to pituitary adenoma cell invasion via targeting c‐Met

Abstract: The current study aimed to evaluate the expression and role of miR-212 in the progression of pituitary adenoma (PA), thereby providing a theoretical basis and potential therapy methods for PA patients. Our data showed that miR-212 levels were significantly reduced in PA tissues than normal pituitary tissues. However, no significant difference was identified in the serum of PA patients and healthy control. In addition, the expression of miR-212 in invasive PA was significantly lower than that in noninvasive and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Up-regulating the target of miR-137 significantly inhibits the proliferation and migration of IPA cells (5). Meanwhile, other studies have also pointed out that a variety of miRNAs are differentially expressed in IPA tissues or cells, including miR-16 (6), miR-106b (7), miR-212 (8), miR-133 (9), and miR-410 (10). It has been found that the expression of miR-183 is imbalanced in a variety of nervous system tumor tissues or cells, which affects the invasion and migration ability of cancer cells (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Up-regulating the target of miR-137 significantly inhibits the proliferation and migration of IPA cells (5). Meanwhile, other studies have also pointed out that a variety of miRNAs are differentially expressed in IPA tissues or cells, including miR-16 (6), miR-106b (7), miR-212 (8), miR-133 (9), and miR-410 (10). It has been found that the expression of miR-183 is imbalanced in a variety of nervous system tumor tissues or cells, which affects the invasion and migration ability of cancer cells (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%